Some Regularities in Climatic and Ecosystem Changes in Siberia - Mikhail V. Kabanov (Журнал Сибирского федерального университета: Серия Биология, 2008)
Applying statistical analysis to instrumented data accumulated in the world meteorological network, we revealed regularities of climatic and ecosystems changes observed in Siberian region. It was shown that warming, observed in Siberia over last climatic period (30 years), is characterized by inhomogeneous subregional structure with mesoscale spots having accelerated warming rates up to 0.5 °С/10 years. Trends of surface pressure for the same period have lesser contrast subregional structure with decrease of annual mean pressure down to 0.2-0.4 hPa/10 years. Wavelet analysis applied to time variability of climatic parameters over the past century found out periodicities with the scales of 10-12 and 30-50 years. Comparing wavelet spectra of surface temperature in West Siberia and North-Atlantic Oscillation index, we revealed their correlation in 1940-1990 with time shift up to 7 years. This climatic phenomenon could be explained by possible inertia mechanisms in oceanic heat transfer. Based on results of ground and airborne and spaceborne instrumented observations, we discuss climatic influence of Siberian bogs (using Great Vasyugan Bog as an example).